Effects of Physical Activity and Inactivity on Muscle Fatigue - Bogdanis, Gregory C. (Frontiers in Physiology, 2012)
The aim of this review was to examine the mechanisms by which physical activity and inactivity modify muscle fatigue. It is well known that acute or chronic increases in physical activity result in structural, metabolic, hormonal, neural and molecular adaptations that increase the level of force or power that can be sustained by a muscle. These adaptations depend on the type, intensity and volume of the exercise stimulus, but recent studies have highlighted the role of high intensity, short duration exercise as a time-efficient method to achieve both anaerobic and aerobic/endurance type adaptations. The factors that determine the fatigue profile of a muscle during intense exercise include muscle fibre composition, neuromuscular characteristics high energy metabolite stores, buffering capacity, ionic regulation, capillarization and mitochondrial density. Muscle fiber type transformation during exercise training is usually towards the intermediate type IIA at the expense of both type I and type IIx myosin heavy chain isoforms. High intensity training results in increases of both glycolyic and oxidative enzymes, muscle capilarization, improved phosphocreatine resynthesis and regulation of K+, H+ and lactate ions. Decreases of the habitual activity level due to injury or sedentary lifestyle result in partial or even compete reversal of the adaptations due to previous training, manifested by reductions in fibre cross-sectional area, decreased oxidative capacity and capillarization. Complete immobilization due to injury results in markedly decreased force output and fatigue resistance. Muscle unloading reduces electromyographic activity and causes muscle atrophy and significant decreases in capillarization and oxidative enzymes activity. The last part of the review discusses the beneficial effects of intermittent high intensity exercise training in patients with different health conditions to demonstrate the powerful effect exercise on health and well being.